Platelet activation in different clinical forms of the coronary artery disease: roll of -Selectin and others platelet markers in the stable and unstable angina - Soeiro, Alexandre de Matos; Araujo, Leila Fernandes; Venturinelli, Margareth L.; Serrano Júnior, Carlos Vicente (Revista de Medicina, 2006)
PURPOSE: Markers of platelet activation are elevated in coronary artery disease.We sought to identify the presence and the potential associations of different markers of platelet activation. METHODS: We studied patients with unstable angina (n = 28), patients with stable angina (n = 36) and patients without coronary artery disease (n = 30); sex and age matched. Blood levels of the adhesion molecule P-selectin, Thromboxane B2 and Serotonin were measured by enzyme immunoassays. RESULTS: When we compared the groups the results were: sP-selectin, thromboxane B2 and serotonin levels were significantly higher in patients with unstable angina than in patients with stable angina. CONCLUSION: These markers of platelet activation were able to identify unstable forms of coronary artery disease.